2020
DOI: 10.3390/cancers12040961
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Aldehyde Dehydrogenases to Eliminate Cancer Stem Cells in Gynecologic Malignancies

Abstract: Gynecologic cancers cause over 600,000 deaths annually in women worldwide. The development of chemoresistance after initial rounds of chemotherapy contributes to tumor relapse and death due to gynecologic malignancies. In this regard, cancer stem cells (CSCs), a subpopulation of stem cells with the ability to undergo self-renewal and clonal evolution, play a key role in tumor progression and drug resistance. Aldehyde dehydrogenases (ALDH) are a group of enzymes shown to be robust CSC markers in gynecologic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 151 publications
0
39
0
Order By: Relevance
“…These cells contained 2.8–10.0% ZIP4 + cells ( Figure 2 A). As a comparison, ALDH activity sorting was also included, since it is widely accepted as an EOC CSC marker [ 7 , 36 ] ( Figure 2 A). These cells contained 1–6% ALDH + cells, consistent with a previous publication [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…These cells contained 2.8–10.0% ZIP4 + cells ( Figure 2 A). As a comparison, ALDH activity sorting was also included, since it is widely accepted as an EOC CSC marker [ 7 , 36 ] ( Figure 2 A). These cells contained 1–6% ALDH + cells, consistent with a previous publication [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, DCA treatment inhibited the expression of stemness master regulators (Oct4, CD133, Sox2) (Figure 1E‐H). Furthermore, ALDH activity was suppressed in CRC cells treated with DCA, which has been shown to be markedly higher in CSC than in parental cancer cells 29,30 (Figure 1I).…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that DS inhibits the P-gp extrusion pump, blocks NF-κB, sensitizes to chemotherapy, decreases angiogenesis, and reduces tumor growth in mice [ 215 ]. DS is able to inhibit both ALDH2 and ALDH1 isozymes, which are upregulated in CSCs, suggesting the potential use of DS as an antineoplastic drug [ 237 ]. Numerous papers have reported DS anti-cancer effects in different tumors (widely reviewed in [ 216 , 217 ]).…”
Section: Csc-targeting Therapeutic Approachesmentioning
confidence: 99%